From Myth to Maṣlaḥah: Customary Prohibitions, Islamic Legal Principles, and Ecological Sustainability in Minangkabau - Warman, Arifki Budia; Rizal, Rizal; Yasrizal, Yasrizal; Kasmuri, Kasmuri; Bahri, Syamsul (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
This research examines how customary prohibitions (larangan adat) embedded in the Minangkabau indigenous tradition function as an ecological governance mechanism rooted in both myth and the Islamic principle of maṣlaḥah (public benefit). Drawing on ethnographic fieldwork conducted in selected nagari (traditional villages) in West Sumatra, this research investigates the ontological and normative significance of tabooed spaces, sacred species, and ritualized ecological restrictions as tools for preserving environmental balance. Through in-depth interviews with customary leaders (ninik mamak), religious scholars (alim ulama), and community members, the research reveals that mythic narratives serve to sacralize ecological zones, while the invocation of maṣlaḥah gives these taboos normative legitimacy within the broader Islamic ethical system. This research argues that customary prohibitions operate as localized ecological jurisprudence, establishing a framework for human–nature relations based not on state law but on a syncretic system of belief that is collectively enforced and symbolically charged. Rather than dismissing these prohibitions as archaic superstition, this research reinterprets them as part of an enduring epistemology that integrates myth, religious values, and environmental pragmatism. This research contributes to the growing body of scholarship on indigenous environmental governance by offering a nuanced reading of adat–myth relations in the context of sustainability. It demonstrates how the Minangkabau adat system far from being static continues to adapt, negotiate, and assert relevance amid ecological crises and modern legal frameworks. Ultimately, this research affirms that myth, when interwoven with religious rationality, can serve as a powerful force for ecological resilience and cultural continuity.